Assessment of sediment and water quality in Sembrong Reservoir, Johor - Syed Hashim, Syarifah Intan Najla (2018)
Sembrong reservoir is a major water source for 240,000 people in the district of Kluang and parts of Batu Pahat. Depletion of storage capacity due to the sedimentation process and eutrophication has recently been the most concerning issues at the reservoir. The objectives of this research are to analyze the distribution of sediment and sedimentation rate in Sembrong reservoir by using GIS. Also, to determine the sediment nutrients and trophic status index (TSI) in Sembrong reservoir in order to correlate the relationship between water and sediment nutrient parameters. Before conducting the laboratory testing, sampling process were done involving sediment and water sampling. Six (6) locations for sediment sampling were selected and portable gravity corer was used to get the sediment cores while for water sampling, seventeen (17) locations were chosen and samples were taken using grab method. Before conducted the laboratory testing, sediment cores were digested to change it state from solid to liquid. Laboratory testing for sediment samples consist of Total Nitrogen (TN), Total Phosphorus (TP) and sieve analysis for particle size distribution. For water samples, in-situ testing was conducted to test for the dissolve oxygen (DO), temperature and pH. Water transparency was tested by using Secchi disc. For laboratory testing, water samples undergo Total Nitrogen (TN), Total Phosphorus (TP), Ammonia Nitrogen, Nitrate and Chlorophyll-a for TSI tests. Data obtained from the testing were analyzed using bathymetry map analysis to determine the sedimentation rate and pattern in Sembrong reservoir for the past years from 1984 to 2013, GRADISTAT for particle size distribution, Carlson‘s trophic status for TSI and SPSS for the correlation between water and sediment nutrient parameters. Based on the 1984 and 2013 bathymetry maps, the reservoir storage capacity was reduced by 12.54 million m3 due to sedimentation. This is equal to 0.43% decrease in volume per year. Surface areas of the reservoir undergo shrinkage as much as 1.216 km for 29 years, thus the rate of shrinkage was 41.83 m/year. Estimation of reservoir useful life shows that Sembrong reservoir is still able to operate up to 20 years from 2013 if there is no action taken. From GRADISTAT analysis, particle size distribution in Sembrong reservoir consist of sandy gravel. For the vertical nutrient composition in sediment, the highest composition of total phosphorus (TP) was obtained at Location 4 in Zone II with 31.41 mg/L at depth of 10 cm from surface while for total nitrogen (TN), the highest composition was also obtained at Location 4 in Zone II with 38.45 mg/L. Sembrong reservoir generally had high nutrient concentrations in the uppermost sediment layers and decreased by sediment depth. The Carlson‘s trophic status analysis had indicated that Sembrong reservoir was in a eutrophic state with TSI > 50 and graded as bad. For correlation analysis by using SPSS, water and sediment nutrient parameters have a weak relationship with r between 0 – 0.2. As conclusion, preventive action and maintenance should be done to remove the sediment and extend the lifespan of Sembrong reservoir. This analysis gave an insight into the variability of sediment nutrient concentration within the reservoir. It also demonstrates the relationship where water may influence the sediment nutrient in the reservoir.